Endovascular management of unruptured intracranial aneurysms: does outcome justify treatment?. Issue 4 (1st April 2002) - Goddard, A J P; Annesley-Williams, D; Gholkar, A
Abstract : Objective: The appropriate management of unruptured intracranial aneurysms depends on a complete understanding of their natural history and on the risks and efficacy of treatment options. There is little current data on the risks of endovascular therapy for these aneurysms. The aim of this study was to assess outcome of endovascular treatment of unruptured intracranial aneurysms. Method: A retrospective analysis was performed on all unruptured aneurysms treated by Guglielmi detachable (GD) coils at this institution from 1994 to 2000. Results: Seventy three unruptured aneurysms were treated in 62 patients. There were 52 female and 10 male patients, with a median age of 55.7 years. Clinical background was: subarachnoid haemorrhage due to rupture of an additional aneurysm (40), headache (4), third nerve palsy (four), familial (four), and incidental (10). There were 14 technical failures with no clinical sequelae. Four procedural complications occurred (5.5%, 95% confidence interval (95% CI) 0.3% to 10.9%). One patient had temporary clinical sequelae (1.4%, 95% CI 0% to 2.7%); 79% of treated aneurysms had stable occlusions at follow up, 10.5% showed improved occlusion grade, 10.5% showed some recurrence, and three patients have required retreatment. Follow up modified Glasgow outcome scores were grade 1, 71%; grade 2, 18%; grade 3, 3%; grade 4, 3%. There were no deaths or haemorrhages during the follow up period. Two patients died as a result of complications from subarachnoid haemorrhage. Conclusion: The endovascular treatment of patients with unruptured aneurysms is safe with few clinical or procedural complications. Poor outcomes were only seen in those patients who presented with subarachnoid haemorrhage due to rupture of an aneurysm at another site.